Attitude and altitude control of quadrotor MAV using FOPID controller - Noordin, Aminurrashid; Mohd Basri, Mohd Ariffanan; Mohamed, Zaharuddin; Mat Lazim, Izzuddin (2024)
This paper presents the implementation of a Fractional Order Proportional-Integral-Derivative (FOPID) controller for attitude and altitude stabi- lization of a quadrotor Micro Air Vehicle (MAV). FOPID extends the conventional Proportional-Integral-Derivative (PID) form by introducing fractional orders to enhance control. It maintains the basic structure of PID with the addition of λ for integration order and µ for differential order, allowing for the study of system performance and increased ﬂexibility in controller design. The simulation in this study utilizes the Fractional-order Modeling and Control (FOMCON) toolbox in MATLAB. At the same time, the system’s performance is assessed through the measurement of Integral Square Error (ISE) and Integral Square Control Input (ISCI). Regarding attitude control, the FOPID controller performs better transient response, and ISE is comparable to the PD controller. However, when considering ISCI, the Proportional-Derivative (PD) controller consumes less energy. Regard- ing altitude control, the FOPID controller performs better ISE but exhibits a 35% overshoot compared to the PD controller. However, the energy consumption of the FOPID controller is not too signiﬁcant compared to the energy consumption of the PD controller.